PENERAPAN SANKSI TERHADAP ANGGOTA POLISI YANG MELAKUKAN KEKERASAN TERHADAP JURNALIS SAAT DEMONSTRASI DI INDONESIA - Widya Kus Anggraini; Mukhlis R; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Journalists or journalists are people who do journalistic work, it turns out that there is still no guarantee of protection for journalists while carrying out their journalistic duties even though it has been explicitly regulated in Law Number 40 of 1999 concerning the Press. Violence committed by police officers is not processed and sanctions are not implemented, because the police themselves do not want to investigate these causes because it will damage the image of the police. Meanwhile, the application of sanctions against police who commit violence against journalists has been regulated in Government Regulation Number 2 of 2003 concerning the Technical Implementation of General Courts for Members of the Indonesian Police.This research is structured using the juridical normative research type, which is research focused on examining the application of the norms or norms in positive law. The approach used in this study is to use a normative juridical approach, namely literature law research, using the protection principle normative research type. Sources of data in this study are secondary legal materials and are assisted by primary and tertiary legal materials. The data analysis used by researchers is qualitative analysis, which is the data analyzed by not using statistics or numbers describing descriptively. The author draws a deductive conclusion, namely drawing conclusions from general matters to specific mattersThe results of this study, based on Government Regulation No. 2 of 2003 concerning the Technical Implementation of General Courts for Members of the Indonesian Police, have regulated sanctions for the police. However, the application of sanctions to police officers who commit acts of violence against journalists is very loose and weak in imposing sanctions. The absence of sanctions against police officers who commit violence against journalists, does not provide a deterrent effect to unscrupulous police officers. With the existence of criminal provisions in Law Number 40 of 1999, it should have provided a sense of security to journalists in carrying out their journalistic duties.Keywords: Sanctions Application, Police, Journalist, Violence